Spiritual Capital in Entrepreneurial Spirit of Dayak Youth - (Reni) Tjondro Sugianto, H A; Vasantan, P (KnE Social Sciences, 2018)
Bengkayang is a regency in a border of Indonesia and Malaysia that has an underdeveloped status. Therefore, Bengkayang needs more people who dare to join the entrepreneurial world. However, since the beginning Dayak people who are the majority in Bengkayang rarely want to enter the business world. This research will reveal why it happened and how to instill entrepreneurial spirit among Dayak youth who become the future of the nation and Bengkayang in particular. This research uses qualitative approach and triangulation method to maintain data reliability. Apparently, growing entrepreneurial spirit in Dayak students is not impossible because they have spiritual capital that can give birth to Social Capital. Social capital is very conducive in creating a business network. As a communal society, the entrepreneurial spirit can be developed through an institutional economic approach which is formed by social capital. Keywords: spiritual capital, social capital, qualitative